AB0638 ABSENCE OF LUNG INVOLVEMENT IN SYSTEMIC SCLEROSIS PATIENTS WITH SILICONE IMPLANTS. (June 2019) - Braun-Moscovici, Yolanda; Braun, Marius; Markovits, Doron; Balbir-Gurman, Alexandra
Abstract : Background: Although many cases have been reported for the last 3 decades, the correlation between silicone breast implants (SBI) and systemic sclerosis (SSc) is yet unclear. Objectives: To assess the prevalence of breast implants in a well characterized SSc cohort followed at a dedicated tertiary center and to define charcteristics that might differ between SSc patients with implants and those without. Methods: A prospectively maintained database was interrogated regarding the prevalence of breast implants and the disease characteristics. Female patients aged 20 to 55y (215 patients) followed at our center between 2003-2018 were included. SBI cases were identified and their characteristics tabulated. Each SBI patient was matched with 2 controls matched for age, disease duration and type of disease. We used descriptive statistics, multivariate comparisons and multivariate analysis for correlations. Results: 11 pts with SBI were found, 6 with diffuse (median age 37.5, range 32-55, median disease duration 3.5 y, range 1.5-8y, median mRSS 13.5, range 8-26) and 5 with limited SSC (median age 38, range 33-45, median disease duration 8y, range 3-22y, mRSS 2, range 2-5). The prevalence of SBI in the 20 to 55 y cohort is 5%, similar to the estimated prevalence in the general population. All had their implants instilled before the diagnosis of SSC (median 10y, range 4-13y). Four pts were first diagnosed with SSC within a year from diagnosis of silicon leakage. RNA polymerase 3 was positive in 3 patients, Scl70 in 3 others, anticentromere in 1 patient and 4 others were positive only for antinuclear antibody. There were no differences in the prevalence of digital ulcers, gastrointestinal involvement, skin score or the serologic profiles between the two groups. However, none of the SBI pts developed interstitial lung involvement, compared to 72% of the matched diffuse patients (p=0.001). There were neither renal crises in the SBI group (compared to 5 cases in the matched group) nor cardiac involvement. Conclusion: The temporal relation and the different clinical features might generate a theory that silicone might induce a particular type of SSC, as the idea that silicone protects against lung involvement seems unreasonable. We plan a further prospective study. Disclosure of interests: None declared